Material screening for the development of a photovoltaic module using biodegradable materials from renewable raw materials - Pander Matthias; Koepge Ringo; Jaeckel Bengt; Mordvinkin Anton (EPJ Photovoltaics)
The development of photovoltaic (PV) modules made of bio-degradable materials from renewable resources offers numerous advantages. It reduces the ecological footprint of the photovoltaic industry and promotes its sustainability. The use of these materials reduces the use of non-renewable resources and minimizes the environmental impact during the full life cycle of the PV module. One limitation of PV modules made from renewable raw materials is their typical limited durability compared to conventional PV modules. Due to their natural properties, biodegradable materials may not offer the same longevity and resistance to environmental influences as conventional materials. This can lead to a shortened lifespan of the modules and affect their long-term performance. The aim of this work is to present a screening of possible material candidates that may be suitable for achieving at least partially substitution of components of standard crystalline PV module with recycled, bio-based or bio-degradable materials. The focus lies on encapsulation, backsheet and module frame as replacement for aluminum. It is shown how these materials behave under the standard requirements of the PV industry, which materials are generally suitable and which mechanisms could prove to be showstoppers. The selected wood-based material as substitute for aluminum showed resistance in aging tests, but the dependence of the properties on the moisture content must be considered. In the design process differences to aluminum regarding fracture behavior must be considered with appropriate design safety factors. From 6 initial variants for mini-module manufacturing only two were identified for further investigation. Material weaknesses were identified in long-term IEC 61215-2 Damp Heat (DH) tests and the sequential test Sequence B of IEC 61730-2. The variant of EVA with bio-degradable additive and bio-based backsheet and polyamid based backsheet were identified as suitable for further testing. The tested bio-degradable materials were identified as not suitable because the temperature and humidity involved in the standard tests lead, even after short testing intervales, to severe material degradation. As result, the materials could no longer fulfill its protective function for the cells.